Implications Fraud Diamond in Fraudulent Financial Statements on Property, Real Estate and Building Construction Industries - Rizki Khoerunnisa, Amalia; Yovita Ariani (APTISI Transactions on Management (ATM), 2024)
Fraudulent financial statements involve intentional actions of manipulating or hiding information in financial reports to deceive users. Understanding the factors behind such fraud can be explored through the Diamond Scheme Theory, consists of four materials: opportunity, rationalization, ability, and pressure. The aim of this research analyze the impact of each component of the Fraud Diamond on fraudulent financial statements. The quantitative research methodology focuses on industries in the real estate, construction and property sectors listed on the Indonesia Stock Exchange starting 2020 to 2022. The sample includes 69 companies selected through purposive sampling. Utilizing multiple linear regression analysis using SPSS 26 is employed for analysis. The study results reveal that, individually, only the capability variable within the Fraud Diamond has a significant negative impact on fraudulent financial statements. Pressure, opportunity, and rationalization variables do not show a significant influence. Additionally, when considered collectively, there is no discernible impact of the Fraud Diamond components on fraudulent financial statements.